ANALISIS ETIKA BERKONSUMSI PADA MAKANAN DAN MINUMAN(Studi Kasus Pada Mahasiswa/ mahasiswi Universitas Islam Sumatera Utara) - Afriza Ulfa Ritonga; Sri Rahmanita Pulungan (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
Ethics is an assessment of the nature of a person who is good and in accordance with morals or good actions and applies in society. Consumption is an activity that consumes the value of an item or service, such as: food, drink, clothing and others. So the ethics of consumption is spending or consuming products that are lawful and good, prioritizing maslahah and simplicity. In today's society there are many people who do not use ethical consumption. So that it is rare that we can find people who use ethical consumption, one might even say they don't exist at all. What a loss for us who do not know what path we will accept if we do not practice consumption ethics properly and correctly. Rasulullah SAW. It has forbidden us about good consumption ethics and that is also explained in the Qur'an. So let's not forget the ethics of consumption, especially if we forget it, it will have an impact on our health